Role of green lacewings and ants on coffee berry borer predation - Botti, Jéssica Mayara Coffler (2021)
The coffee berry borer (CBB) Hypothenemus hampei is the most severe pest of the coffee crop in the world. Larvae open galleries inside the endosperm of coffee fruits, causing significant losses in yield and fruits quality. In addition, control of this pest is hampered due to its cryptic habit of living inside the fruits. The reduction the sources of shelter and alternative food for predatory insects that carry out the biological control of CBB is due to the simplification of the landscape associated with conventional coffee crops. Therefore, it is necessary to use measures that aim to decrease these problems caused by the implantation of conventional crops, in order to increase and maintain the CBB natural enemies in these areas. Among these measures, landscape diversification, through strategic diversification with plants that can provide food resources and shelter to natural enemies. In this work, a strategic diversification in coffee crops was implemented, without the use of pesticides, associated with Inga edulis, Varronia currasavica, Senna macranthera and non-crop plants, recognized for favoring the biological control of CBB through the maintenance of predatory ants in the area. During field evaluations, an adult of the Chrysopidae family was found that emerged from a coffee bored berries collected in the diversified coffee crop area. In Chapter I, I confirmed the hypothesis that naked larvae the of Chrysoperla externa are able to enter the galleries and remove CBB eggs and larvae from inside the fruits, proving to be efficient in pest control. In Chapter II, I tested whether the behavior of transporting debris on the back reduces the access to the CBB galleries by trash-carry larvae of Ceraeochrysa cubana in relation to C. externa. The results showed that the first instar larvae of the two species (C. externa and C. cubana) are able to enter the CBB galleries and survive longer in the presence of coffee bored berries than in the presence of healthy berries and without food. However, C. cubana was less efficient in entering the galleries, showing that the trash can limit the predation of CBB inside the fruit. Third instar larvae of C. externa preyed on CBB adults and reduced the capacity of CBB to infest the fruits by 10%, which shows that C. externa can be more efficient in controlling the CBB due to its ease of accessing the galleries. In the Chapter III I evaluated the richness and abundance of predatory ants of CBB, the rate of infestation of CBB and the coffee yield in the diversified system implemented, comparing it to the conventional coffee system. The results showed thatstrategic diversification increased predator ant richness and abundance, decreased CBB infestation and did not affect coffee yield. Therefore, strategic diversification with I. edulis, V. currasavica, S. macranthera and non-crop plants increases the natural control of CBB by predatory ants and green lacewings, in addition to not reducing coffee yield. Keywords: Hypothenemus hampei. Conservative biological control. Chrysopidae.